New Games via soft-I-Semi-g-Separation axioms - Mohammad, R.J.; Esmaeel, R.B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this article, the notions are introduced by using soft ideal and soft semi-open sets, which are - - - -closed sets " -closed" where many of the properties of these sets are clarified. Some games by using soft- -semi, soft separation axioms: like ( 0 ( 0 Using many figures and proposition to study the relationships among these kinds of games with some examples are explained.